1988
DOI: 10.1111/j.1600-051x.1988.tb01590.x
|View full text |Cite
|
Sign up to set email alerts
|

The predominant cultivable microbiota of active and inactive lesions of destructive periodontal diseases

Abstract: Subgingival plaque samples were taken from active and inactive lesions in 33 subjects exhibiting active destructive periodontal diseases. Active diseased sites were those which showed a significant loss of attachment within a 2-month interval as computed by the "tolerance method". The predominant cultivable species from 100 active sites were compared with those found in 150 inactive sites of comparable pocket depth and attachment level loss. Among the 33 subjects, W. recta, B. intermedius, F. nucleatum, B. gin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
434
1
7

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 664 publications
(455 citation statements)
references
References 46 publications
13
434
1
7
Order By: Relevance
“…Since these organisms have an important role in oral infection, their isolation and identification are required (12,18). Periodontal bacteria such as E. corrodens, A. actinomycetemcomitans, P. gingivalis, P. intermedia and F. nucleatum are recognized as important opportunistic pathogens in the development of periodontal and non-oral diseases of humans and dogs (7,16,19).…”
Section: Discussionmentioning
confidence: 99%
“…Since these organisms have an important role in oral infection, their isolation and identification are required (12,18). Periodontal bacteria such as E. corrodens, A. actinomycetemcomitans, P. gingivalis, P. intermedia and F. nucleatum are recognized as important opportunistic pathogens in the development of periodontal and non-oral diseases of humans and dogs (7,16,19).…”
Section: Discussionmentioning
confidence: 99%
“…A shift in the microbial community leading to outgrowth of this anaerobe is directly linked to periodontitis, a chronic inflammatory disease that leads to destruction of the tissues supporting the gums and ultimately, exfoliation of the teeth (Choil et al, 1990;Dzink et al, 1988;Grossi et al, 1994;Lamont & Jenkinson, 2000;Moore et al, 1991). This commensal can colonize, invade and multiply within gingival epithelial cells, as well as penetrate into deeper epithelial cell layers, potentially releasing the whole organism and/or virulence factors into the bloodstream (reviewed by Yilmaz, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Fusobacterium species play a central role in biofilm formation, mediating coaggregation between early and late colonizers (5,6,7). Fusobacterium species including F. nucleatum, are detected in high frequency in lesions of gingivitis and chronic periodontitis (8,9). P. intermedia and Prevotella nigrescens are frequently isolated from the periodontal lesions of patients with chronic periodontitis (8,9,10), aggressive periodontitis (11,12), puberty-associated gingivitis (13,14), and acute necrotizing ulcerative gingivitis (15).…”
Section: Introductionmentioning
confidence: 99%
“…Fusobacterium species including F. nucleatum, are detected in high frequency in lesions of gingivitis and chronic periodontitis (8,9). P. intermedia and Prevotella nigrescens are frequently isolated from the periodontal lesions of patients with chronic periodontitis (8,9,10), aggressive periodontitis (11,12), puberty-associated gingivitis (13,14), and acute necrotizing ulcerative gingivitis (15). Recently, our research group reported that the average number of periodontopathic bacterial species, including P. intermedia and P. nigrescens, was significantly higher in plaque samples 5 harboring F. nucleatum and/or F. periodontium than in those without in Japanese children and mothers (16).…”
Section: Introductionmentioning
confidence: 99%